Moving with the times: amending the ICSID rules - Meg Kinnear (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2018)
ICSID is amending its rules for resolving international investment disputes. This Perspective outlines changes proposed by the ICSID Secretariat in August 2018, which draw on input from governments, the private sector and the public. The proposals update ICSID's existing rules for arbitration, conciliation and fact-finding, and introduce new mediation rules.
Keywords: 330